Mathematical Problem Solving with Technology Beyond the Classroom: The use of Unconventional Tools and Methods - Jacinto, Hélia (2018)
This paper addresses mathematical problem solving with technologies in a beyond school web-based competition. We aim to disclose the ways mathematical and technological knowledge are used and combined for solving the given problems. A specific conceptual framework for accounting both these components was developed. By means of the Mathematical Problem Solving with Technology model (MPST) we report the case of Marco, aged 13, solving and expressing a geometrical problem. His ability in perceiving affordances in the tools that he chose is in line with the eficient use he made of them in the development of mathematical understanding that was crucial for finding and expressing the solution. Results suggest that digital thinking and experience have to be seen as relevant as the mathematical cognitive resources.